Pengembangan Buku Suplemen Fisika Berbasis Kearifan Lokal Untuk Meningkatkan Literasi Sains Peserta Didik SMAN 5 Wajo - Fauziah; Jasruddin Daud Malago; M. A. Martawijaya (Jurnal Penelitian Pendidikan IPA, 2025)
One of the local wisdoms of the Bugis tribe that is still often found in Wajo district is a traditional food that they call Putu Soppa' or Putu Tongka. The objectives of this study were: to describe the profile of a valid local wisdom-based physics supplement book for students of SMAN 5 Wajo; to describe teacher responses to the use of local wisdom-based physics supplement books for students of SMAN 5 Wajo that have been developed; to describe student responses to the use of local wisdom-based physics supplement books for students of SMAN 5 Wajo that have been developed. This study is a development researchs using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was implemented in class XI IPA 2 of SMAN 5 Wajo. Data collection was carried out through observation/interviews, expert assessments, questionnaires and science literacy tests. Then analyzed using descriptive analysis. The results of this study indicate that: the developed teaching materials are declared valid with a reliability level of 0.72; the practicality of teaching materials reviewed from the practitioner's response shows that the developed teaching materials are practical with a percentage of 0.90; the effectiveness of the developed teaching materials is reviewed from the learning outcomes of students obtained through learning outcome tests (science literacy tests). A classical percentage of 80.64% or 25 out of 31 students achieved the learning completion criteria was obtained. So, reviewed from the number of students who achieved completion, the teaching materials are declared effective.